A Dry Platform for Separation of Proteins from Biomass‐Containing Polysaccharides, Lignin, and Polyphenols. Issue 7 (11th March 2015) - Barakat, Abdellatif; Jérôme, François; Rouau, Xavier
<x xml:space="preserve">Abstract</x> License to mill: Proteins were continuously extracted from polysaccharides, lignin, and polyphenol by combining ultrafine milling with electrostatic separation. Such a fractionation process does not involve any solvent, catalyst, or external source of heating. In addition, this dry process is compatible with downstream enzymatic reactions, thus opening an attractive route for producing valuable chemicals from biomass.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>